Debt and Personal Financial Management of Elderly People in Thailand - ปาอ้าย อำนวย (Community and Social Development Journal, 2018)
ABSTRACT The purpose of this research were 1) to study the elderly’s debt and financial management, 2) to study the financial management behaviors of the elderly in Thailand, and 3) to compare the financial management behaviors of the elderly with their demographic data. The sample were elderly people from the eastern region of Thailand, consisted of 400 people using multi-stage sampling method. The tools used in the data collection were questionnaires. The data analysis included : frequency, percentage, mean, standard deviation, t-test and F-test. The Results of the research were as follows : 1) Most of the elderly were female, farmers, Had primary education. Had a marital status and earn no more than 10,000 baht per month. 2) Most elderly people had sources of income from their offspring or relatives. Had property as a house, Had savings of up to 100,000 baht. Monthly expenses not exceeding 5,000 Baht, receive a living allowance of more than 500 Baht per month, expenses for food. No debt, No financial problems and no financial need. 3) Elderly people had financial management behaviors and spending money financing. Savings and investment and all inclusive Is less practical Except for debts, financial and debt management behaviors. Stay in a non-operational level. 4) Elderly with different sex. Had financial and debt management behaviors. not different The elderly with different age, occupation, status and income had different financial and debt management behaviors at .001 level of significance.